Identification of a new disease cluster of pemphigus vulgaris with autoimmune thyroid disease, rheumatoid arthritis and type I diabetes. (1st March 2015) - Parameswaran, A.; Attwood, K.; Sato, R.; Seiffert‐Sinha, K.; Sinha, A.A.
Summary: Background: Pemphigus vulgaris (PV) is a potentially fatal autoimmune blistering skin disease. It is known that individuals with autoimmune diseases such as PV, as well as their family members, are at increased risk of developing other autoimmune diseases. However, it is unknown whether there are specific autoimmune diseases that cluster with PV. Objectives: To investigate the frequency of coexisting autoimmune diseases in patients with PV and their relatives, to determine the prevalence of specific autoimmune diseases in patients with PV vs. the general population and to identify statistically significant clinical clusters linking PV with other autoimmune disorders. Methods: We performed a cross‐sectional study and meta‐analysis of patient data from our own patient database ( n = 230), an anonymous online survey conducted by our laboratory ( n = 171) and the International Pemphigus & Pemphigoid Foundation registry ( n = 393). Results: We found that the prevalences of autoimmune thyroid disease (AITD), rheumatoid arthritis and type 1 diabetes were significantly increased in patients with PV compared with the general population. These diseases were also among the most frequent in family members of patients with PV, in addition to systemic lupus erythematosus (SLE). Descriptive cluster analysis using basic principle components methods revealed that PV forms a distinct cluster with AITD, rheumatoid arthritis and type 1 diabetes, and another cluster with SLE, AITD and rheumatoid arthritis. Conclusions: PV belongs to an established autoimmune disease cluster that includes AITD, rheumatoid arthritis and type 1 diabetes. Our data suggest the possibility of common genetic elements across clinically distinct diseases that might underlie autoimmune susceptibility.